2009
DOI: 10.1007/s00468-009-0376-2
|View full text |Cite
|
Sign up to set email alerts
|

Looking for differences in wood properties as a function of the felling date: lunar phase-correlated variations in the drying behavior of Norway Spruce (Picea abies Karst.) and Sweet Chestnut (Castanea sativa Mill.)

Abstract: A large-scale field experiment on the drying behavior of Norway Spruce (Picea abies Karst.) and Sweet Chestnut (Castanea sativa Mill.) in relation to the felling date was conducted over a period of 24 weeks in order to investigate the existence of variations linked to lunar rhythms, which are mentioned as having a role in many traditional forestry practices. The measured criteria were the water loss from fresh to dry state, the shrinkage linked to this water loss, and the relative density (ratio between the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…The period was 26–31 days, which corresponds to the period of the synodic lunar cycle (29.5 days). For comparison, in vascular plants, the lunar cycle affects a wide range of biological processes, such as flowering and pollination (Rydin and Bolinder , Ben‐Attia et al ), tissue electrical conductivity (Burr , Holzknecht and Zürcher ), the content of water and chemical elements in the tissues (Vogt et al , Zürcher et al ), as well as shoot growth (Maw , Abrami ). However, among the bryophytes, S. riparium is the first representative to have circalunar rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…The period was 26–31 days, which corresponds to the period of the synodic lunar cycle (29.5 days). For comparison, in vascular plants, the lunar cycle affects a wide range of biological processes, such as flowering and pollination (Rydin and Bolinder , Ben‐Attia et al ), tissue electrical conductivity (Burr , Holzknecht and Zürcher ), the content of water and chemical elements in the tissues (Vogt et al , Zürcher et al ), as well as shoot growth (Maw , Abrami ). However, among the bryophytes, S. riparium is the first representative to have circalunar rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…This applies not only with respect to food management, where water percent in plant fruits and leaves often affects their flavor, maturation, and storage (Kollerstrom and Staudenmaier 2001), but also for the management of tree wood quality (Zürcher 2001). With respect to this lastmentioned quality, the mechanical properties of timber have been found to be strictly correlated to the water content of wood at the time of tree felling (Zürcher et al 2010); this biological variable has been shown to be modulated in accordance with the phase of the Moon.…”
Section: Introductionmentioning
confidence: 99%
“…Relationship between circalunar rhythmicity and LSC. Terrestrial plants have demonstrated sensitivity to LSC in flowering and pollination (Rydin & Bolinder, 2015;Ben-Attia et al, 2016), electrical conductivity of tissue (Burr, 1947;Holzknecht & Zürcher, 2006), the content of moisture and elements in tissues (Vogt et al, 2002;Zürcher et al, 2010), shoot growth and movement (Maw, 1967;Abrami, 1972;Buda et al, 2001).…”
Section: Discussionmentioning
confidence: 99%